1978
DOI: 10.1136/jmg.15.2.85
|View full text |Cite
|
Sign up to set email alerts
|

A family study of vesicoureteric reflux

Abstract: SUMMARY Vesicoureteric reflux is now considered to be due essentially to congenital malformation of the vesicoureteric junction. It is also considered to be a major cause of renal failure in early adult life. The condition is associated with recurrent urinary tract infection and in some instances with renal scarring. When reflux is detected clinically, in the investigation of patients with recurrent urinary tract infection, renal scarring is often already present. The reflux tends to disappear in later childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…73 Feather et al concluded that the VUR phenotype may result from an alteration in a number of different genes on different chromosomes. 73 Early family segregation studies suggested that more than one genetic alteration may be responsible for VUR in some families 74,75 It appears that in some families VUR can result from one DNA change, whereas in others more than one DNA change is required. Given the genetic variability, phenotypic variability is not surprising.…”
Section: Developmental Aspectsmentioning
confidence: 99%
“…73 Feather et al concluded that the VUR phenotype may result from an alteration in a number of different genes on different chromosomes. 73 Early family segregation studies suggested that more than one genetic alteration may be responsible for VUR in some families 74,75 It appears that in some families VUR can result from one DNA change, whereas in others more than one DNA change is required. Given the genetic variability, phenotypic variability is not surprising.…”
Section: Developmental Aspectsmentioning
confidence: 99%
“…Therefore, the Gly691Ser mutation could generate a spectrum of deficiencies of ureteral development manifesting as incomplete penetrance of disease phenotype. The possible genetic causes of the disease in the remaining 29% of patients in our group who do not carry the Gly691Ser mutation could include mutations in the unscreened regulatory regions of RET, deficiencies of another gene or multiple genes involved in urinary tract development [Devriendt et al, 1998;Eccles and Jacobs, 2000;Burger and Smith, 1971;Chapman et al, 1985;Eccles, 1998;Jerkins and Noe, 1982;de Vargas et al, 1978]. For example, the disruption of ROBO2 was recently found to confer risk of VUR [Lu et al, 2007].…”
Section: Discussionmentioning
confidence: 97%
“…This increased to 50% and 100%, respectively, when only the youngest individuals were considered [Stephens et al, 1955;Mebust and Foret, 1972;Uehling et al, 1992;Connolly et al, 1996;Kaefer et al, 2000]. Numerous studies failed to firmly establish the inheritance pattern of pVUR and it is unclear whether it is a monogenic or a polygenic disorder [Middleton et al, 1975;de Vargas et al, 1978;Jerkins and Noe, 1982;Chapman et al, 1985;Devriendt et al, 1998;Eccles and Jacobs, 2000;Pasch et al, 2004]. Despite the wide range of approaches used, very few predisposing genes or regions are known, either because only few families showed linkage to genes or regions studied or due to lack of published evidence to connect data generated in animal studies to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that VUR can occur in families, and genetic factors likely play an important role in the pathogenesis (9 -11,16). Different modes of inheritance of VUR have been suggested, including a dominant single gene and polygenic inheritance (27)(28)(29). Although cases of 13q deletion syndrome have been identified occasionally with renal malformations, VUR and ESRD previously have not been associated with 13q deletion (30 -33).…”
Section: Discussionmentioning
confidence: 99%